Coordinación de protecciones en Sistemas Eléctricos de Distribución considerando la introducción de generación distribuida - Mayorga Lozada, Nicolas Alejandro (2023)
Distribution systems are constantly growing, so it is important to implement new generation technologies to satisfy all demand. Distributed Generation (DG) is a strong alternative in Ecuador, since the country has abundant natural resources for renewable energy generation, however, the inclusion of DG to the electrical network affects the operating values and short-circuit currents, therefore to the coordination of the existing electrical protection system and consequently it is necessary to carry out a readjustment for its proper functioning.